The Transformational Potential of Higher Education Inclusion - Biographical Trajectories of Students from Disadvantaged Environments in Venezuela - Pineda Olivieri, Jesús Humberto (Universitätsverlag Göttingen, 2017)
In the field of higher education research, one of the most fascinating observations is the consistent and permanent expansion of higher education systems worldwide since the end of the Second World War. Undoubtedly, the predominant approach to address these developments has been through quantitative analysis, as well as international comparisons. The following work examines the particularities of the Venezuelan context with the aim of identifying specific features of this worldwide phenomenon in this South American case. Through a combination of qualitative methods, the author proposes a biographical approach for the study of higher education inclusion processes, which takes into account the perspectives and experiences of those who have been targeted by an ambitious higher education expansion process. The most distinctive feature of this work would be its methodological contribution to the field of higher education research. One could also argue that the ethnographic account of the Bolivarian Missions of education in Chavez's Venezuela is both original and unprecedented. Furthermore, the writing approach bridges the interests of both academics, practitioners of the field and members of the general public.